EFFECT OF TIO2 WEIGHT ON THE EFFICIENCY OF DYE SENSITIZED SOLAR CELL (DSSC) USING NAVICULA SP. TAD MICROALGAE AS NATURAL DYE. - SAMUEL M. TARIBUKA; EKA R.M.A.P LILIPALY; IVONNE TELUSSA (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2023)
Electricity requirements increase every year and have become a necessity for every household in the world. Alternative electricity sources will be required to handle the need. New and renewable energy (NRE) offer divers source on this issue; however, the development of these sources demands more exploration. DSSC or Dye Sensitized Solar Cell as the third generation of Solar Cell is one of the sources that can be explored. Using Microalgae as its dye is known to be an excellent choice for alternative natural dye. Navicula TAD, the original type of Microalgae found in Ambon Bay has been proven to be able to be a catalyst in electricity flow on DSSC. This research is investigating the effect of TiO2 paste weight on the efficiency of DSSC that uses Navicula TAD as the natural dye. Early studies showed that as the weight of TiO2 paste increases, the efficiency also increases. Using TiO2 weight of 0.1; 0.3 grams, the greatest efficiency is found in the DSSC with 0.3 grams of paste. The efficiency of DSSC with 0.3 grams of TiO2 paste is 17.02%.